GAMBARAN KEPUASAN MASYARAKAT TERHADAP TENAGA KESEHATAN PELAYANAN COVID-19 DI KABUPATEN SUMBAWA - Rusmayady (Jurnal Kesehatan dan Sains, 2022)
The level of patient satisfaction with hospital services in Indonesia during the Covid-19 pandemic has not yet reached the minimum service standard.Hospital readiness and preparedness in the face of the Covid-19 pandemic are needed to achieve quality services so as to increase patient satisfaction. The purpose of this study was to find out the description of community satisfaction with health workers for Covid 19 services in Sumbawa Regency in 2021. The type of research used was qualitative. Data collection techniques using in-depth interviews. The informants in this study were Covid-19 patients. The results showed that the community was satisfied with the services provided by health workers in terms of service procedures, friendliness, comfort and discipline of health workers.